A review on ergonomic assessment tool at small and medium enterprise (SME) industries - Zayyinul Hayati, Zen; Widia, Mirta; Ezrin Hani, Sukadarin (Springer, 2021)
An ergonomic assessment is a foundation for designing a comfortable workplace, which is safer and healthier with less injuries, optimized wellbeing, and improved overall workplace performance. Previous studies showed that most of the ergonomic assessment tools assess physical risk factors related to Musculoskeletal Disorder (MSD). It is interesting to investigate other ergonomic risk factors that are important to include in an ergonomic assessment tool that is related to workers’ productivity in SME industries. This study set out to review the ergonomic assessment tools that have been widely used in Small and Medium (SME) Industries. To achieve the study objective, the review was conducted by searching the Google Scholar and Science Direct database. About 83 articles were identified in the first process. However, only 25 articles are included in this study after the screening process. The review found that there is lacking assessment on other ergonomic risk factors, such as psychosocial and cognitive risk factors that would also contribute to workers' productivity. Many ergonomic assessment tools that have been used in Small and Medium (SME) Industries only focused on assessing the physical risk factors that affect MSD. The knowledge and understanding of various ergonomic assessment tools will help the researchers plan the next step to improve the tool that will assess the significant ergonomic risk factors that affect worker's productivity. It might help to establish a common set of ergonomic assessment tools that are more effective, efficient, and user-friendly